Feasibility of Supplying Ruminally Protected Lysine and Methionine to Periparturient Dairy Cows on the Efficiency of Subsequent Lactation - Elsaadawy, Samy A.; Wu, Zhaohai; Bu, Dengpan (Frontiers in Veterinary Science, 2022)
The objective of this study was to evaluate the effects of supplying ruminally protected Lys (RPL) and ruminally protected Met (RPM) to transition cows' diets on the efficiency of subsequent lactation. A total of 120 prepartum Holstein cows were assigned into four treatments blocked by the anticipated calving date, previous lactation milk yield, number of lactations, and body condition score and fed either RPL, RPM, or the combination (RPML) or control diet (CON) throughout the transition period (3 weeks before till 3 weeks after calving). From 22 to 150 days in milk (DIM), all animals (100 cows) were fed a combination of RPM and RPL (0.17% RPM and 0.41% RPL of DM; n = 25 cows/treatment) as follows; CON–RPML, RPM–RPML, RPL–RPML, and RPML–RPML. Milk production and dry matter intake (DMI) were measured daily; milk and blood samples were taken at 21, 30, 60, 90, 120, and 150 DIM. Supplemented amino acids (AA) were mixed with the premix and added to the total mixed ration during the experiment. DMI (p < 0.001) and energy-corrected milk (ECM, p = 0.04) were higher for cows that were fed RPML–RPML than other cows. Compared with CON–RPML, yields of milk total protein, lactose, and nitrogen efficiency were increased (p < 0.01), whereas milk urea nitrogen (MUN; p = 0.002) was decreased for other treatments. However, supplemental AA did not affect milk lactose percentage, fat yield, feed efficiency, or serum total protein concentration (p > 0.10). Transition cows that consumed AA had a greater peak of milk yield (p < 0.01), as well as quickly reached the peak of milk (p < 0.004). There were differences in β-hydroxybutyrate concentration during the early lactation, with a lower level for AA groups (p < 0.05), and the difference faded with the progression of lactation (p > 0.10). Fertility efficiency as measured by pregnancy rate was improved by supplemental AA during the perinatal period (p < 0.05). In conclusion, transition cows consumed RPM and RPL, increased post-calving DMI, milk production, milk protein yield, nitrogen efficiency, and improved fertility performance.